Population dynamics of small mammals in the Jura massif, Franche-Comté, France (1979-2000) - Pierre Delattre; Patrick Giraudoux; Jean-Pierre Quéré; Jean-Pierre Damange (Zenodo, 2022)
Small mammal populations were monitored seasonally from August 1979 to July 2000 according to a stratified sampling plan and using standard trapping, mostly in the area of Septfontaines – Le Souillot, Doubs, France (6.18°E, 46.97°N). The dataset includes 2120 trap lines (90% n = 1912 in the Septfontaines – Le Souillot (LS) area), and 22848 captures (92% n = 20937 in the LS area). Methods Small mammals were captured using INRA trap lines. INRA live traps (15 × 5 × 5 cm) are suitable for species of body mass less than 50 g. In a standard way generally applied here,each trap line consisted of 34 live traps spaced 3 meters apart. Trap lines were set up for three nights and checked every morning. Animals were euthanized by cervical dislocation, weighed and dissected for sex, reproductive status and age determination. Liver was examined macroscopically for parasites. Relative age was estimated based on the dry weight of crystalline eye lenses. Caveats: in a very little number of cases (beginning of the study and circumstantial occasions) trap lines were not standard (150 m length, 51 traps, or set up for one or two nights only, etc.). See Codes_Trapline.docx and fields "remarques" (table traplines.txt ) and 'observation' (table captures.txt ). Sometimes field not informed have been coded "", 99 or NA. Although we did our best to harmonize this in the files uploaded, some inconsistencies might remain. Those issues should be considered carefully before data analysis. Trapping and animal handling was carried out in full accordance with the relevant European guidelines (Directive 86/609/EEC) and national regulations. INRA ( Institut National de la Recherche Agronomique ), the umbrella organization under which the field work was carried out, created its first ethical committee in 1998. It was therefore impossible to get formal ethical approval prior to the major part of the study. A similar research protocol used from 2014 to 2017 received full approval from the Comité d’Éthique Bisontin en Expérimentation Animale (CEBEA ...